Antioxidant activity of Cheddar cheese during its ripening time and after simulated gastrointestinal digestion as affected by probiotic bacteria. Issue 1 (1st January 2019) - Chen, Ping; Liu, Lu; Zhang, Xiuxiu; Massounga Bora, Awa Fanny; Li, Xiaodong; Zhao, Mingqi; Hao, Xinyue; Wang, Yu
ABSTRACT: The purpose of our study was to evaluate the effect of the addition of Lactobacillus casei and Lactobacillus plantarum to Cheddar cheese on the antioxidant properties during its ripening time and after simulated gastrointestinal conditions. During the whole ripening time, the scavenging of DPPH and hydroxyl radicals both reached their maximum activity at the 16th week, while reducing power activity was reached at the 20th week. The antioxidant values of probiotics cheese were significantly higher than that of control ( p < 0.05). Similar results were found after simulated gastrointestinal conditions. The simulated gastric digestion can significantly reduce the activity of DPPH radicals-scavenging ( p < 0.05), but after intestinal condition, the values came back to the same level compared with that before digestion. The electrophoretic patterns indicated that adding probiotic to cheese could promote the hydrolysis of protein to enhance the antioxidant activity, especially with mixed probiotics. The addition of probiotic bacteria to Cheddar cheese had nearly no effect on its composition, texture proï¬le analysis, and sensory analysis.